Addition of Medicinal Weeds in The Ration on Broiler Chicken Performance - Nurhayati, Nurhayati; Nelwida, Nelwida; Handoko, H (ANIMAL PRODUCTION, 2009)
An experiment was conducted to compare the effect of feeding medicinal weeds namely bandotan, patikan kebo and sidaguri on broiler chickenâs performance. The experiment used 100 broiler chicken 3 days of age and were kept for 5 weeks in battery cages. Each cage was 100 x 80 x 60 cm of size and consist 5 chickens. Design of this experiment was assigned to Completely Randomized Design (CRD) with 4 treatments and 5 replications. The treatments were R0 (Basal ration without medicinal weed), R1 (95% basal ration + 5% bandotan (Ageratum conyzoides L)), R2 (95% basal ration + 5% patikan kebo (Euphorbia hirta L)) dan R3 (95% basal ration + 5% sidaguri (Sida cordifolia)). Ration and drinking water were ad libitum. Measured parameters were feed consumption, average daily gain and feed conversion ratio. Data were analyzed by analysis of variance (ANOVA) and the significant effects by Duncanâs multilple range test (DMRT). Results of this study showed that feeding 5% of medicinal weeds either bandotan, patikan kebo or sidaguri had similarly effect (P>0,05) on feed consumption, average daily weight gain and feed conversion ratio of broiler chicken. However, bandotan and sidaguri resulted average daily weight gain lower than patikan kebo. It is concluded that medicinal weeds bandotan, patikan kebo and sidagu could be fed to the chicken up to 5% without significant effect on broiler performance. Patikan kebo resulted better broiler performance than that of bandotan and sidaguri. (Animal Production 11(2): 103-108 (2009)Â Key Words: Ageratum conyzoides, Euphorbia hirta L, sida cordifolia, weeds